Attitudes of family firms toward outside investors: the importance of organizational identification. Issue 1 (2nd January 2017) - Neckebrouck, Jeroen; Manigart, Sophie; Meuleman, Miguel
Abstract: More and more family firms open their capital for outside investors, yet existing studies mainly conclude that family firms are more reluctant than nonfamily firms to hand over control to outside investors. In this study, we build on an organizational identification perspective to explore why family firms differ in their attitudes toward outside investors. We hypothesize that family members who identify strongly with their firms are less willing to cede control to outside investors and, if they do cede control, have a stronger preference for investors who may readily identify with family firms, such as family offices or high net worth individuals, rather than investors who may not fit well with a familial identity, such as private equity sponsors or financial investors. We also hypothesize that social identification mediates the relationship between important family firm governance characteristics and preferences for outside investor. Exploratory evidence from a sample of Belgian family firms is supportive of most of our predictions.